The F238L point mutation in the cannabinoid type 1 receptor enhances basal endocytosis via lipid rafts - Wickert, Melanie; Schneider, Miriam (Frontiers in molecular neuroscience, 2018)
Defining functional domains and amino acid residues in G protein coupled receptors (GPCRs) represents an important way to improve rational drug design for this major class of drug targets. The cannabinoid type 1 (CB1) receptor is one of the most abundant GPCRs in the central nervous system and is involved in many physiological and pathophysiological processes. Interestingly, mutagenesis of phenylalanine 238 to a leucine (CB1F238L) has been already linked to a number of both in vitro and in vivo alterations. While CB1F238L causes significantly reduced presynaptic neurotransmitter release at the cellular level, behaviorally this mutation induces increased risk taking, social play behavior and reward sensitivity in rats. However, the molecular mechanisms underlying these changes are not fully understood. In this study, we tested whether the F238L mutation affects trafficking and axonal/presynaptic polarization of the CB1 receptor in vitro. Steady state or ligand modulated surface expression and lipid raft association was analyzed in HEK293 cells stably expressing either CB1wt or CB1F238L receptor. Axonal/presynaptic polarization of the CB1F238L receptor was assessed in transfected primary hippocampal neurons. We show that in vitro the CB1F238L receptor displays increased association with lipid rafts, which coincides with increased lipid raft mediated constitutive endocytosis, leading to a reduction in steady state surface expression of the CB1F238L receptor. Furthermore, the CB1F238L receptor showed increased axonal polarization in primary hippocampal neurons. These data demonstrate that endocytosis of the CB1 receptor is an important mediator of axonal/presynaptic polarization and that phenylalanine 238 plays a key role in CB1 receptor trafficking and axonal polarization.
Gesehen am 16.03.2020